SEISMIC RESPONSE OF REINFORCED CONCRETE TALL BUILDINGS - Syed Wasim Nawaz Razvi (International Journal of Innovations in Engineering Research and Technology, 2022)
Earthquakes present one of the most devastating hazards on the planet. They threaten the safety of civilians in seismically active regions, and are of extreme concern in applications that demand a high level of safety, i. e. the nuclear industry. However, in nearly all cases, the fatalities that occur are as a result of the collapse of man-made structures. Hence the problems facing Civil Engineers who are concerned with seismic mitigation is evident. Seismic engineering research and application has progressed rapidly over the last few decades, not least in part due to the evolution of computer technology, and our ability to produce computer models which aid us in the design and analysis processes. Hence the research presented focuses on the global behaviour of a typical statically designed tall reinforced concrete building. A literature review has been performed to investigate current mathematical and experimental work which has been carried out with regard to reinforced concrete structures under seismic/cyclic loading. In this paper, the seismic behavior of reinforced concrete tall building is presented. The 5,7,9 and ,11 storey concrete buildings with six frames in each direction has been analyzed for static, modal and time-history analyses under a typical (synthetic) earthquake by popular structural design software “STAAD Pro 2007”. The buildings are analyzed firstly with Slab-beam-column structure, and secondly for without beam i.e. as flat slab construction and thirdly flat slab construction with shear wall. This has resulted in to analyzing 12-models. The results are compared with each other for natural time period, Sa/g, Story drift, base shear & column forces. The test results suggest that buildings with beam-column system have better seismic performance than buildings without beam i.e. as flat slab system.